Frequency Distribution of Oncology Patients Who Come to Emergency Department at H. Adam Malik Hospital, Medan - Kamal Basri Siregar; David Restu Manik; Luqmanul Hakim; Habib Solihin Gultom; Muhammad Naqib bin Md Ghazali (Sumatera Medical Journal, 2024)
Background: A multidisciplinary approach is needed to comprehensively evaluate cancer patient’s condition and understanding patient demographic characteristics can improve health care by adapting to each patient's needs. Objective: The aim of this study was to explore about frequency distribution of oncolohy patients. Methods: This research is a descriptive observational study with a cross-sectional study design conducted at the Haji Adam Malik General Hospital in Medan on oncology patients who met the inclusion criteria. Data with a numerical measuring scale will be presented in mean+standard deviation (SD) and data with a categorical measuring scale will be presented in frequencies and percentages. Results: The results showed that majority of patients were in 46–59 year age group as much as 32 patients (37.2%) and 58 patients (67.4%) were female. The highest level of education was found in 26 patients (30.2%) as bachelor, and 45 patients (52.3%) lived in Medan City. Most patients came to be treated at the surgical installation as many as 50 patients (25.6%). Conclusion: The research results found that majority of patients are in the age group 46-59 years, female, bachelor, domicile in Medan and are treated in surgical installation.